(untitled) - 1971-; Baron Cohen, Sacha; Smith, Jada Pinkett; 1966-; 1971-; the Entertainer; 1965-; Richter, Andy; 1966-; Zimmer, Hans; Schwimmer, David; Cedric; et al. (Universal City, CA, 2005)
A lion and zebra and two other of their pampered friends, from New Yorks Central Park Zoo, accidentally find themselves on a ship heading for Africa. When their vessel is hijacked, they become shipwrecked on the exotic island of Madagascar where they discover it really is a jungle out there!
Keywords: Drama; Madagascar; Animals; Drama; Madagascar; Jungles; Madagascar; Drama; Madagascar; Shipwrecks; Drama; Zoo animals; Juvenile drama; Africa; Juvenile drama; Madagascar; Childrens films; Video recordings for the hearing impaired; Childrens; Animation; Feature; Drama; Animated films; Video recordings for the hearing impaired; Feature films; Childrens; Animation; Feature; Video recordings; Childrens films; Animated films; Drama; Feature films; Juvenile works